2006
DOI: 10.1557/jmr.2006.0321
|View full text |Cite
|
Sign up to set email alerts
|

Properties of ceramics in the system ZrB2–Ta5Si3

Abstract: Ceramics in the system ZrB 2 -Ta 5 Si 3 were studied as candidates for the development of new ultra high-temperature ceramic materials. The ceramics were prepared by hot pressing at 1900-2200°C in He. Mutual additions of ZrB 2 and Ta 5 Si 3 even in small amounts had significant densifying effects due to chemical interactions and solid solubility between the components, which have not been reported in the literature. Materials containing between 8 and 30 vol% Ta 5 Si 3 exhibited less oxidation than pure ZrB 2 ,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
43
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 3 publications
5
43
0
Order By: Relevance
“…( 6). This solution phase has been previously observed [8,10] and is reasonable since both ZrB2 and TaB2 have a hexagonal crystal structure. XRD results showed that the (100), (101), and (111) peaks for ZrB2 all exhibited shoulders displaced by 0.1 to 0.5 degrees 2theta higher indicating reduction of the lattice parameters of the hexagonal ZrB2 structure with the introduction of TaB2…”
Section: Substrate Before Oxidationsupporting
confidence: 86%
See 2 more Smart Citations
“…( 6). This solution phase has been previously observed [8,10] and is reasonable since both ZrB2 and TaB2 have a hexagonal crystal structure. XRD results showed that the (100), (101), and (111) peaks for ZrB2 all exhibited shoulders displaced by 0.1 to 0.5 degrees 2theta higher indicating reduction of the lattice parameters of the hexagonal ZrB2 structure with the introduction of TaB2…”
Section: Substrate Before Oxidationsupporting
confidence: 86%
“…(3). Talmy et al [7][8][9] attribute similar observations of glass immiscibility to Ta additions to the system. EDS analysis [10] of the immiscible phases in Fig.…”
Section: Optimization Of Tasi2 Contentmentioning
confidence: 86%
See 1 more Smart Citation
“…SiO 2 ðlÞ þ COðgÞ (2) respectively. Intense research is ongoing to characterize and enhance this scale as a barrier against oxygen [11][12][13][14][15][16][17][18][19][20][21][22][23] (the scale microstructure can be seen in, for example, Fig. 4 of Opila et al 15 ), which apparently is superior to that of either monolithic diboride or SiC at the intended high temperatures (see Fig.…”
mentioning
confidence: 99%
“…Ta 5 Si 3 provides the tantalum to induce glass immiscibility and silicon to form the protective borosilicate glass in the oxidized layer. [39] ZrB 2 -and HfB 2 -TaSi 2 composites have been formed by hot pressing, [40] resulting in formation of a solid solution as the tantalum entered the boride matrix. The HfB 2 -TaSi 2 displayed superior mechanical properties to the ZrB 2 -based material.…”
Section: Using Alternatives To Sic To Introduce Siliconmentioning
confidence: 99%